Implementation of Islamic Economic Principles in Islamic Financial Institution - Rinda Asytuti; Sakiyah Gusriani; Asna Muzayyanah; Itsna Maulidal Faza; Habibah, Ummu (International Journal of Economics (IJEC), 2026)
This study analyzes the substantive implementation of Islamic economic principles in Islamic financial institutions based on the framework of Maqashid al-Shariah.A qualitative case study approach was employed, collecting data through in-depth interviews and document analysis. The findings indicate that the principle of wealth protection is realized through the avoidance of riba and gharar, although operational activities are more heavily dominated by sale-based contracts rather than profit-sharing arrangements. On the other hand, the integrated social function is carried out through the management of ZISWAF, yet its implementation often faces pressure to meet profitability targets. Tensions arise between adhering to formal procedures and achieving the intended benefits.